The Beauty of Patience and Gratitude Based on the Hadith narrated by Imam Muslim from Abu Suhaib Bin Sinan - Ma'arif, Muhammad Ghozali; Reza Pratama; Muhammad Shahbaz Hassan (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
Patience and gratitude are noble traits approved by Allah SWT as a means to strengthen one's faith and devotion to the Lord. These qualities elevate His servants in His eyes and guarantee them a place in paradise. This explicitly illustrates the beauty of patience and gratitude as manifestations of Allah's mercy towards His servants. This article aims to describe the beauty of patience and gratitude based on the perspectives of the Quran and the Hadith of the Prophet Muhammad SAW, particularly the essence of the Hadith narrated by Abu Yahya Shuhaib Bin Sinan found in Muslim's Hadith collection. This research falls under the category of literature review. In Islamic teachings, patience (sabr) is considered a highly esteemed attribute. The Holy Quran and the sayings of Prophet Muhammad provide guidance to the Muslim community to practice patience in the face of trials and life's challenges. Endurance in coping with various tribulations is viewed as an indicator of strong faith and a means to attain great rewards in the hereafter. Allah SWT states in the Quran, Surah Al-Baqarah (2:153), "O you who have believed, seek help through patience and prayer. Indeed, Allah is with the patient." Additionally, the virtue of gratitude (al-shukr) is also emphasized in Islamic teachings. Allah SWT repeatedly reminds humankind to express gratitude for the blessings bestowed upon them.